Sites of Violence : Gender and Conflict Zones - Hyndman, Jennifer; Giles, Wenona Mary, 1949- (Book collections on Project MUSE., 2004)
Augmenting feminist analysis on conflict zones, this volume explores the gendered politics of ethno-nationalism 'honour-killings' in Iraq & Kurdistan, the civil war in Sudan & geographies of violence in Ghana, to investigate what happens when violence is invoked against people.